Positive electrode material and preparation method thereof, and lithium ion battery
By regulating the particle size distribution and free lithium stability of the nickel-cobaltate-based composite oxide positive electrode material, combined with the modification treatment of free lithium ion converter, the problem of poor circulation performance of high-nickel positive electrode materials in the prior art is solved, and excellent circulation performance and cost-reducing effect are achieved.
Patent Information
- Application Number
- CN202311803462.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-12-25
AI Technical Summary
The existing doping and coating processes are difficult to effectively improve the cycling and electrochemical properties of high-nickel cathode materials, and are costly.
The lithium nickel-cobaltate-based composite oxide is used as the positive electrode material, and the cyclic performance of the positive electrode material is improved by regulating the peak area ratio P and the free lithium stability coefficient L in its particle size distribution curve, combined with the modification treatment of the free lithium ion converter.
The excellent circulation performance of the nickel-cobaltate lithium-cobaltate positive electrode material has been achieved, which solves the problem of poor circulation performance in the prior art, and reduces costs.
Smart Images

Figure CN117936771B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the increasingly serious global energy crisis and environmental pollution, countries have called for reducing carbon emissions and developing sustainable clean energy to replace traditional fossil energy. As a new type of high-energy green battery, lithium-ion batteries have the characteristics of high energy density, long cycle life, and wide application range compared with traditional energy batteries. In recent years, lithium-ion batteries have developed rapidly under the government's strong subsidies and the stimulation of new energy market demand. As the core part of lithium-ion batteries, positive electrode materials determine the overall performance of lithium-ion batteries. The development of positive electrode materials with excellent performance has always been a research hotspot.
[0003] High nickel positive electrode materials have the advantages of high voltage platform and high specific capacity, and are the most promising positive electrode materials for large-scale application in the power battery market. However, as the proportion of nickel continues to increase, the negative conditions of the positive electrode materials such as cation mixing and residual alkali will be aggravated, which will affect the electrochemical properties such as the cycle stability of the positive electrode materials, and will cause battery safety problems, thus limiting the application of high nickel positive electrode materials in the power battery market. To this end, technicians in this field have studied the use of doping and coating processes to modify high nickel positive electrode materials to improve their electrochemical properties; among them, the doping process generally improves the cycle stability and other electrochemical properties of high nickel positive electrode materials by doping one or more elements into the structure of high nickel positive electrode materials; the coating process is to coat one or more elements on the surface of the high nickel material, and then remove the residual lithium on the surface of the high nickel positive electrode material by washing or chemical reaction, so as to form a coating layer on the surface of the high nickel material that is conducive to ion transmission, thereby effectively slowing down the side reactions at the electrode / electrolyte interface and improving the cycle performance of the material. However, in the existing doping and coating process modification process, there are at least the following problems: (1) compatibility issues between dopants and the main structure; (2) the problem that dopants have a great impact on the conductivity and reaction activity of the high-nickel positive electrode material itself; (3) the water washing treatment in the existing coating process will cause the impedance of the positive electrode material to increase during the cycle process, making it difficult for lithium ions to be inserted and removed, and even destroying the structural stability; (4) the coating process is relatively complicated, which will lead to increased costs.
[0004] Therefore, the existing doping and coating process modifications are still difficult to significantly improve the electrochemical properties such as the cycle performance of high-nickel positive electrode materials, cannot meet the ideal target requirements, and there is also the problem of high cost.
[0005] Application Contents
[0006] The present application provides a positive electrode material and a preparation method thereof, and a lithium-ion battery, which can improve the cycle performance of nickel-cobalt-oxide lithium positive electrode materials.
[0007] In a first aspect, the present application provides a positive electrode material, wherein the positive electrode material is a nickel-cobalt-lithium oxide composite oxide;
[0008] The particle size distribution curve of the positive electrode material has a first characteristic peak and a second characteristic peak, the peak area of the first characteristic peak is A1, the peak area of the second characteristic peak is A2, and P=A2 / A1;
[0009] The free lithium stability coefficient of the positive electrode material is L, L = (L1-L2) / L1, and the test method of L1 and L2 is: take 5g of the positive electrode material and disperse it in 100ml of deionized water, stir it magnetically for t min, and filter the filtrate to determine the free lithium content; when t = 60, the mass content of free lithium in the positive electrode material is measured to be L1, and when t = 10, the mass content of free lithium in the positive electrode material is measured to be L2;
[0010] The positive electrode material satisfies the following relationship: 10≤P*L≤25.
[0011] In some embodiments, the chemical formula of the positive electrode material is: LiNi a Co b Mn c M d N e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, and the M includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, Nb, and the N includes at least one of W, B, Mo, F, S, V, P and Cl.
[0012] In some embodiments, the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material, the base material is a composite oxide including Ni, Co, Mn and M elements, and the M element includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb.
[0013] In some embodiments, the coating layer includes a lithium salt, the chemical formula of which is Li x N y O z , wherein x, y, z>0, and N includes at least one of W, B, Mo, F, S, V, P and Cl.
[0014] In some embodiments, in the positive electrode material, 0.25≤L≤0.85.
[0015] In some embodiments, in the positive electrode material, 0.15%≤L1≤0.45%.
[0016] In some embodiments, in the positive electrode material, 0.02%≤L2≤0.16%.
[0017] In some embodiments, in the positive electrode material, 8≤P≤50.
[0018] In some embodiments, in the positive electrode material, 4≤A1≤25.
[0019] In some embodiments, in the positive electrode material, 150≤A2≤250.
[0020] In some embodiments, the conductivity of the positive electrode material is 0.025 S / cm to 0.080 S / cm.
[0021] In some embodiments, the compaction density of the positive electrode material is 3.10 g / cm 3 ~3.65g / cm 3 .
[0022] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g~0.8m 2 / g.
[0023] In a second aspect, the present application also proposes a method for preparing a positive electrode material, comprising the following steps:
[0024] A free lithium ion conversion agent is added to an aqueous solution of a base material for modification treatment, wherein the amount of the free lithium ion conversion agent added is 0.6wt%-1.2wt% based on the mass of the base material as 100wt%, and a precursor is obtained by solid-liquid separation; wherein the base material is a nickel cobalt acid lithium composite oxide, and the particle size distribution curve of the base material has a first characteristic peak and a second characteristic peak, the peak area of the first characteristic peak is A1, the peak area of the second characteristic peak is A2, P=A2 / A1, 8≤P≤50;
[0025] The precursor is sintered to obtain a positive electrode material.
[0026] In some embodiments, in the aqueous solution of the matrix material, the mass of deionized water is 15% to 30% of the mass of the matrix material.
[0027] In some embodiments, the matrix material is a composite oxide including Li, Ni, Co, and Mn elements.
[0028] In some embodiments, the step of preparing the matrix material includes: preparing a mixture material including a ternary precursor and a lithium source, and sintering the mixture material under an oxygen atmosphere to obtain the matrix material.
[0029] In some embodiments, the oxygen flow rate of the oxygen atmosphere is 200m 3 / h~450m 3 / h.
[0030] In some embodiments, in the step of preparing the matrix material, the furnace pressure of the sintering is 3Pa to 25Pa.
[0031] In some embodiments, in the step of preparing the base material, the sintering includes a constant temperature stage, and the sintering temperature in the constant temperature stage is 600-800°C.
[0032] In some embodiments, the sintering time in the constant temperature stage is 8 hours to 15 hours.
[0033] In some embodiments, in the step of preparing the matrix material, the sintering further includes a heating stage, and the heating rate of the heating stage is 2° C. / min to 5° C. / min.
[0034] In some embodiments, the matrix material is a composite oxide including Li, Ni, Co, Mn and M elements, and the M element includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb.
[0035] In some embodiments, the mixed material includes an M dopant.
[0036] In some embodiments, the chemical formula of the ternary precursor is Ni a Co b Mn c (OH)2, 0.8≤a≤0.98, 0.01≤b≤0.2, 0.01≤c≤0.2.
[0037] In some embodiments, the M dopant includes at least one of Sr(OH)2, SrO, TiO2, Al2O3, Al(OH)3, ZrO2, Zr(OH)4, Ba(OH)2, BaO, MgO, Mg(OH)2, Nb2O5, Nb2O3, WO3 and CaWO4.
[0038] In some embodiments, the mass of the M dopant is 0.1% to 0.55% of the mass of the ternary precursor.
[0039] In some embodiments, the mass of the M dopant is 0.2% to 0.4% of the mass of the ternary precursor.
[0040] In some embodiments, the ternary precursor includes first particles and second particles having different particle sizes, and the particle size D50 of the first particles is 12 μm-18 μm.
[0041] In some embodiments, the ternary precursor includes first particles and second particles having different particle sizes, and the particle size D50 of the second particles is 2 μm-5 μm.
[0042] In some embodiments, the ternary precursor includes first particles and second particles having different particle sizes, and a mass ratio of the first particles to the second particles is 1:(1-5).
[0043] In some embodiments, the lithium source includes at least one of hydrated lithium hydroxide, lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, and lithium oxalate.
[0044] In some embodiments, the molar ratio of the Li element in the lithium source to the ternary precursor is 0.95 to 1.25.
[0045] In some embodiments, the mass of the free lithium ion conversion agent is 0.6%-1.2% of the mass of the matrix material.
[0046] In some embodiments, the free lithium ion conversion agent contains N, and the N includes at least one of W, B, Mo, F, S, V, P and Cl.
[0047] In some embodiments, the free lithium ion conversion agent includes at least one of KAl(SO4)2, NH4HSO4, MgCl2, NH4Cl, CaF2, NH4HF2, NaVO3, NH4VO3, (NH4)3PO4, (NH4)2HPO4, and Ca(H2PO4)2.
[0048] In some embodiments, the modification treatment is performed under an ultrasonic environment.
[0049] In some embodiments, the frequency of the ultrasound wave is 20 kHz to 50 kHz.
[0050] In some embodiments, the ultrasonic time of the ultrasonic wave is 20 min-40 min.
[0051] In some embodiments, the step of preparing the aqueous solution of the matrix material comprises: mixing the matrix material with deionized water and stirring them uniformly, and the stirring speed is 20 Hz to 50 Hz.
[0052] In some embodiments, the stirring time is 20 min to 40 min.
[0053] In some embodiments, during the sintering process of the precursor, the sintering temperature is 250°C to 500°C.
[0054] In some embodiments, during the sintering process of the precursor, the sintering time is 6 hours to 12 hours.
[0055] In some embodiments, the solid-liquid separation includes subjecting the modified mixture to a filter press treatment, and the extrusion pressure of the filter press is 0.2MPa-0.5MPa.
[0056] In some embodiments, the filtration time is 10 min-30 min.
[0057] In some embodiments, after the filter pressing treatment, the solid-liquid separation further comprises drying the filter pressing product.
[0058] In some embodiments, the drying temperature of the drying process is 80°C to 170°C.
[0059] In some embodiments, the drying time of the drying process is 1 hour to 3 hours.
[0060] In some embodiments, the free lithium stability coefficient of the positive electrode material is L, 10≤P*L≤25, wherein L=(L1-L2) / L1, and the test method of L1 and L2 is: take 5g of positive electrode material and disperse it in 100ml of deionized water, stir it magnetically for t min, and filter the filtrate to determine the free lithium content; when t=60, the mass content of free lithium in the positive electrode material is measured to be L1%, and when t=10, the mass content of free lithium in the positive electrode material is measured to be L2%.
[0061] In some embodiments, 0.25≤(L1-L2) / L1≤0.85.
[0062] In some embodiments, 0.15%≤L1≤0.45%.
[0063] In some embodiments, 0.02%≤L2≤0.16%.
[0064] In some embodiments, 4≤A1≤25.
[0065] In some embodiments, 150≤A2≤250.
[0066] In a third aspect, the present application further proposes a lithium-ion battery, comprising the positive electrode material as described above, or comprising the positive electrode material prepared by the preparation method as described above.
[0067] Compared with the prior art, this technical solution has at least the following technical effects:
[0068] The positive electrode materials of the present application include nickel cobalt oxide lithium positive electrode materials including high nickel positive electrode materials, which satisfy the relationship: 10≤P*L≤25, and have the characteristics of excellent cycle performance, which solves the problem that the application of nickel cobalt oxide lithium positive electrode materials is limited due to poor cycle performance in the prior art. During the research process, the applicant discovered through reasoning and verification that: in the positive electrode material (specifically referring to nickel cobalt oxide lithium positive electrode material, the same below), the particle size and the particle matching ratio are important parameters affecting the cycle performance of the positive electrode material; in order to include these multiple parameters affecting the cycle performance of the positive electrode material into the consideration range of the cycle performance of the positive electrode material, so as to achieve an accurate evaluation of the cycle performance of the positive electrode material, this application introduces the peak area ratio P to link the changes of different parameters, solving the problem that the cycle performance is difficult to accurately evaluate due to complex influencing factors, and the introduction of the peak area ratio P can also more intuitively reflect the dynamic changes in the cycle performance of the positive electrode material under the influence of various parameters, making the cycle performance test results of the positive electrode material more valuable for reference; in addition, the applicant also found in the research process: free lithium There is a certain correlation between the stability coefficient L and the peak area ratio P. Changing the peak area A2 or A1 means a change in the grain boundary at the microscopic level, and a change in the contact area from a macroscopic perspective, which will cause the amount of residual alkali generated by the positive electrode material reacting with carbon dioxide and water in the air to change, thereby changing the conversion efficiency of free lithium on the surface of the positive electrode material, and then affecting the structural stability of the positive electrode material. The structural stability of the positive electrode material is a key factor affecting its cycle performance. Therefore, this application incorporates the free lithium stability coefficient into the calculation formula of the positive electrode material cycle performance; the applicant has found through research that the product of the peak area ratio P and the free lithium stability coefficient L has a certain correlation with the cycle performance of the positive electrode material. When 10≤θ=P*L≤25, the positive electrode material has excellent cycle performance and can meet application requirements. This application summarizes the parameters that affect the cycle performance of the positive electrode material into a calculation formula for the cycle performance measurement parameter θ of the positive electrode material, and by regulating and optimizing the correlation coefficient in the calculation formula, the cycle performance measurement parameter θ of the positive electrode material is within the above range, thereby improving the cycle performance of the positive electrode material. In the technical solution of the present application, the cycle performance measurement parameter θ of the positive electrode material can be calculated according to the above formula, and the cycle performance of the positive electrode material can be judged by the value of θ. Since the parameters A1, A2, L1 and L2 involved in the calculation formula can be quickly measured, compared with the conventional test method for the cycle performance of positive electrode materials, the present application evaluates the cycle performance of the positive electrode material by testing A1, A2, L1 and L2, which can greatly shorten the test cycle and test cost.
[0069] In the preparation method of the present application, by regulating the ratio of the peak area A1 of the first characteristic peak to the peak area A2 of the second characteristic peak in the particle size distribution curve of the matrix material, and by adding an appropriate amount of free lithium ion conversion agent to modify the matrix material, the electrochemical properties of the matrix material, such as capacity, conductivity and cycle performance, are comprehensively improved, that is, the electrochemical properties of the modified positive electrode material, such as capacity, conductivity and cycle performance, are excellent and can meet application requirements. During the research process, the applicant discovered through reasoning and verification that: in the nickel cobalt lithium oxide positive electrode material, the particle size and the particle matching ratio are important parameters that affect the cycle performance of the positive electrode material; this application incorporates these multiple parameters that affect the cycle performance of the positive electrode material into the consideration range of the cycle performance of the positive electrode material to achieve an accurate evaluation of the cycle performance of the positive electrode material, but multiple influencing factors will also increase the difficulty of evaluating the material performance. In order to solve this problem, this application creatively introduces the peak area ratio P parameter to link the multiple factors that affect the cycle performance of the positive electrode material; in the positive electrode material, the role of large particles is mainly reflected in increasing the capacity of the positive electrode material, but large particles are also easy to This causes cracks and pores to appear in the positive electrode material during the cycle, thus affecting the cycle performance of the positive electrode material; small particles have better physical stability, can stabilize the structure of the positive electrode material, prevent the positive electrode material from breaking during the cycle, and improve its cycle stability; the appropriate ratio of large and small particles is critical to improving the performance of the positive electrode material: appropriate particle size distribution and particle matching are conducive to a better solid / solid interface between the active substance of the positive electrode material and the electrolyte, thereby accelerating the transmission speed of lithium ions; and the appropriate combination of large and small particles can increase the compaction density of the positive electrode material, improve the mass of active substances per unit volume in the positive electrode material, and help release the electrochemical properties of the positive electrode material. In the process of preparing the positive electrode material, the present application limits the peak area ratio P within an appropriate range by regulating the particle size of the matrix material and the matching ratio of the particles, which is beneficial to the improvement of the cycle performance of the positive electrode material; in addition, in the modification treatment of the matrix material, the added free lithium ion converter will absorb the residual lithium in the matrix material to achieve the regulation of the free lithium in the matrix material, and will react with these free lithium to generate a lithium salt coating layer coated on the surface of the matrix material. These lithium salt coating layers have a stable structure and can optimize the surface structure of the positive electrode material to achieve effective improvement of the cycle performance of the positive electrode material; because in the positive electrode material, an excessively high conversion rate of free lithium will destroy the structural stability of the positive electrode material, causing the positive electrode material to experience internal lattice lithium loss in the layered structure, thereby affecting the cycle performance of the positive electrode material, therefore, in the modification process, the present application controls the addition amount of the free lithium converter within an appropriate range so that the cycle performance of the positive electrode material can be further improved.
[0070] In summary, in the preparation method of the present application, the cycle performance of the positive electrode material is significantly improved by comprehensively regulating the ratio of the peak area A1 of the first characteristic peak to the peak area A2 of the second characteristic peak in the particle size distribution curve of the matrix material and the amount of free lithium converter added. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0072] Figure 1 A process flow chart of the preparation method of the positive electrode material of the present application;
[0073] Figure 2-20 They are the particle size distribution diagrams of Examples 1-11 and Comparative Examples 1-8 respectively;
[0074] Fig.21 1 is the XRD pattern of Example 1 and Example 5;
[0075] Figure 22-25 This is the SEM image of Example 1. DETAILED DESCRIPTION
[0076] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0077] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0078] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0079] It should be understood that the term "and / or" used in this application is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this application generally indicates that the associated objects before and after are in an "or" relationship.
[0080] First aspect. The present application proposes a positive electrode material, which is a nickel cobalt lithium oxide composite oxide, and the particle size distribution curve of the positive electrode material includes a first characteristic peak and a second characteristic peak, the peak area of the first characteristic peak is A1, the peak area of the second characteristic peak is A2, and P=A2 / A1; the free lithium stability coefficient of the positive electrode material is L, L=(L1-L2) / L1, and the test method of L1 and L2 is: take 5g of the positive electrode material and disperse it in 100ml of deionized water, stir it magnetically for t min, and filter the filtrate to determine the free lithium content; when t=60, the mass content of free lithium in the positive electrode material is measured to be L1, and when t=10, the mass content of free lithium in the positive electrode material is measured to be L2; the positive electrode material satisfies the following relationship: 10≤θ=P*L≤25.
[0081] The positive electrode materials of the present application include nickel cobalt oxide lithium positive electrode materials including high nickel positive electrode materials, which satisfy the relationship: 10≤P*L≤25, and have the characteristics of excellent cycle performance, which solves the problem that the application of nickel cobalt oxide lithium positive electrode materials is limited due to poor cycle performance in the prior art. During the research process, the applicant discovered through reasoning and verification that: in the positive electrode material (specifically referring to nickel cobalt oxide lithium positive electrode material, the same below), the particle size and particle matching ratio are important parameters affecting the cycle performance of the positive electrode material; in order to include these multiple parameters affecting the cycle performance of the positive electrode material into the consideration range of the cycle performance of the positive electrode material, so as to achieve an accurate evaluation of the cycle performance of the positive electrode material, this application introduces the peak area ratio P to link the changes of different parameters, solving the problem that the cycle performance is difficult to accurately evaluate due to complex influencing factors, and the introduction of the peak area ratio P can also more intuitively reflect the dynamic changes in the cycle performance of the positive electrode material under the influence of various parameters, making the cycle performance test results of the positive electrode material more valuable for reference; in addition, the applicant also found in the research process: free lithium There is a certain correlation between the stability coefficient L and the peak area ratio P. Changing the peak area A2 or A1 means a change in the grain boundary at the microscopic level, and a change in the contact area from a macroscopic perspective, which will cause the amount of residual alkali generated by the positive electrode material reacting with carbon dioxide and water in the air to change, thereby changing the conversion efficiency of free lithium on the surface of the positive electrode material, and then affecting the structural stability of the positive electrode material. The structural stability of the positive electrode material is a key factor affecting its cycle performance. Therefore, this application incorporates the free lithium stability coefficient into the calculation formula of the positive electrode material cycle performance; the applicant has found through research that the product of the peak area ratio P and the free lithium stability coefficient L has a certain correlation with the cycle performance of the positive electrode material. When 10≤θ=P*L≤25, the positive electrode material has excellent cycle performance and can meet application requirements. This application summarizes the parameters that affect the cycle performance of the positive electrode material into a calculation formula for the cycle performance measurement parameter θ of the positive electrode material, and by regulating and optimizing the correlation coefficient in the calculation formula, the cycle performance measurement parameter θ of the positive electrode material is within the above range, thereby improving the cycle performance of the positive electrode material. In the technical solution of the present application, the cycle performance measurement parameter θ of the positive electrode material can be calculated according to the above formula, and the cycle performance of the positive electrode material can be judged by the value of θ. Since the parameters A1, A2, L1 and L2 involved in the calculation formula can be quickly measured, compared with the conventional test method for the cycle performance of positive electrode materials, the present application evaluates the cycle performance of the positive electrode material by testing A1, A2, L1 and L2, which can greatly shorten the test cycle and test cost.
[0082] In some embodiments, the chemical formula of the positive electrode material is: LiNi a Co b Mn c Md N e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, and M includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, Nb, and N includes at least one of W, B, Mo, F, S, V, P and Cl.
[0083] In some embodiments, the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material, the base material is a composite oxide including Ni, Co, Mn and M elements, and M includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb; the doping of the M element can construct an ion conductor transport layer in the base material, which is beneficial to improving the electrical conductivity of the positive electrode material.
[0084] In some embodiments, the coating layer includes a lithium salt, the chemical formula of the lithium salt is Li x N y O z , wherein x, y, z>0, N includes at least one of W, B, Mo, F, S, V, P and Cl elements; Li x N y O z The coating layer has a stable structure and can effectively improve the cycle performance and safety performance of the positive electrode material.
[0085] In some embodiments, 0.25≤L≤0.85; in the present application, L is the free lithium stability coefficient of the positive electrode material, which is used to measure the stability of the free lithium on the surface of the positive electrode material. If L is too high, the free lithium content on the surface of the positive electrode material is high, and there may be unstable lithium ions inside the positive electrode material, which are easily dissolved, and the stability of the structural functional layer on the surface of the positive electrode material is poor; if L is too low, it means that the lattice lithium in the positive electrode material has suffered a certain loss, causing some stable Li to dissolve, resulting in different test conditions. The measured free lithium content does not change much. In this case, the capacity cycle retention rate of the positive electrode material is easily affected. By limiting L to the above range, it is beneficial to improve the structural stability of the positive electrode material and to greatly improve the cycle performance of the positive electrode material.
[0086] In some embodiments, L1 is 0.15% to 0.45%, specifically 0.15%, 0.25%, 0.35%, 0.45% or any value therebetween.
[0087] In some embodiments, L2 is 0.02% to 0.16%, specifically 0.02%, 0.08%, 0.12%, 0.16% or any value therebetween.
[0088] In some embodiments, 8≤P≤50; in the present application, P is essentially the ratio of the peak area of the volume density occupied by large particles in the positive electrode material to the peak area of the volume density occupied by small particles. In the positive electrode material, the role of large particles is mainly reflected in increasing the capacity of the positive electrode material, but large particles are also prone to cause cracks and pores in the positive electrode material during the cycle, thereby affecting the cycle performance of the positive electrode material; small particles have better physical stability, can stabilize the structure of the positive electrode material, and prevent the positive electrode material from breaking during the cycle, thereby improving its cycle stability; the appropriate ratio of large and small particles is critical to improving the performance of the positive electrode material: appropriate particle size distribution and particle matching are conducive to making the active substance of the positive electrode material and the electrolyte have a better solid / solid interface, thereby accelerating the transmission speed of lithium ions; and the appropriate combination of large and small particles can increase the compaction density of the positive electrode material, improve the mass of the active substance per unit volume in the positive electrode material, and is conducive to releasing the electrochemical properties of the positive electrode material. When the P value is within the above range, the particle size and mixing ratio of large and small particles of the positive electrode material are appropriate, which is conducive to the comprehensive improvement of electrochemical properties such as capacity, conductivity, and cycle performance.
[0089] In some embodiments, A1 is 4-25, specifically 4, 8, 12, 16, 20, 25 or any value therebetween.
[0090] In some embodiments, A2 is 150-250, specifically 150, 200, 250 or any value therebetween.
[0091] In some embodiments, the conductivity of the positive electrode material is 0.025 S / cm to 0.080 S / cm, specifically 0.025 S / cm, 0.040 S / cm, 0.060 S / cm, 0.080 S / cm or any value therebetween.
[0092] In some embodiments, the compacted density of the positive electrode material is 3.10 g / cm 3 ~3.65g / cm 3 , specifically 3.10 g / cm 3 、3.20g / cm 3 、3.30g / cm 3 、3.40g / cm 3 、3.50g / cm 3 、3.65g / cm 3 or any value in between.
[0093] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g~0.8m 2 / g, specifically 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g or any value in between.
[0094] In a second aspect, the present application also proposes a method for preparing a positive electrode material.
[0095] See also Figure 1 In an embodiment of the present application, the method for preparing the positive electrode material comprises the following steps:
[0096] S1. Adding a free lithium ion conversion agent to an aqueous solution of a base material for modification treatment to obtain a modified mixture, and performing solid-liquid separation on the modified mixture to obtain a precursor; wherein the base material is a nickel cobalt lithium oxide composite oxide, and the particle size distribution curve of the base material has a first characteristic peak and a second characteristic peak, the peak area of the first characteristic peak is A1, the peak area of the second characteristic peak is A2, P = A2 / A1, 8≤P≤50;
[0097] S2. Sintering the precursor to obtain a positive electrode material.
[0098] In the above steps, based on the mass of the matrix material as 100wt%, the added amount of the free lithium ion converter is 0.6wt%-1.2wt%, specifically 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt% or any value therebetween.
[0099] It can be understood that in the embodiment of the present application, the free lithium ion converter is a reagent that can convert free lithium in the positive electrode material into lithium salts, and those skilled in the art can select the specific type of the free lithium ion converter as needed.
[0100] In the preparation method of the present application, by regulating the ratio of the peak area A1 of the first characteristic peak to the peak area A2 of the second characteristic peak in the particle size distribution curve of the matrix material, and by adding an appropriate amount of free lithium ion conversion agent to modify the matrix material, the electrochemical properties of the matrix material, such as capacity, conductivity and cycle performance, are comprehensively improved, that is, the electrochemical properties of the modified positive electrode material, such as capacity, conductivity and cycle performance, are excellent and can meet application requirements. During the research process, the applicant discovered through reasoning and verification that: in the nickel cobalt lithium oxide positive electrode material, the particle size and the particle matching ratio are important parameters that affect the cycle performance of the positive electrode material; this application incorporates these multiple parameters that affect the cycle performance of the positive electrode material into the consideration range of the cycle performance of the positive electrode material to achieve an accurate evaluation of the cycle performance of the positive electrode material, but multiple influencing factors will also increase the difficulty of evaluating the material performance. In order to solve this problem, this application creatively introduces the peak area ratio P parameter to link the multiple factors that affect the cycle performance of the positive electrode material; in the positive electrode material, the role of large particles is mainly reflected in increasing the capacity of the positive electrode material, but large particles are also easy to This causes cracks and pores to appear in the positive electrode material during the cycle, thus affecting the cycle performance of the positive electrode material; small particles have better physical stability, can stabilize the structure of the positive electrode material, prevent the positive electrode material from breaking during the cycle, and improve its cycle stability; the appropriate ratio of large and small particles is critical to improving the performance of the positive electrode material: appropriate particle size distribution and particle matching are conducive to a better solid / solid interface between the active substance of the positive electrode material and the electrolyte, thereby accelerating the transmission speed of lithium ions; and the appropriate combination of large and small particles can increase the compaction density of the positive electrode material, improve the mass of active substances per unit volume in the positive electrode material, and help release the electrochemical properties of the positive electrode material. In the process of preparing the positive electrode material, the present application limits the peak area ratio P within an appropriate range by regulating the particle size of the matrix material and the matching ratio of the particles, which is beneficial to the improvement of the cycle performance of the positive electrode material; in addition, in the modification treatment of the matrix material, the added free lithium ion converter will absorb the residual lithium in the matrix material to achieve the regulation of the free lithium in the matrix material, and will react with these free lithium to generate a lithium salt coating layer coated on the surface of the matrix material. These lithium salt coating layers have a stable structure and can optimize the surface structure of the positive electrode material to achieve effective improvement of the cycle performance of the positive electrode material; because in the positive electrode material, an excessively high conversion rate of free lithium will destroy the structural stability of the positive electrode material, causing the positive electrode material to experience internal lattice lithium loss in the layered structure, thereby affecting the cycle performance of the positive electrode material, therefore, in the modification process, the present application controls the addition amount of the free lithium converter within an appropriate range so that the cycle performance of the positive electrode material can be further improved.
[0101] In summary, in the preparation method of the present application, the cycle performance of the positive electrode material is significantly improved by comprehensively regulating the ratio of the peak area A1 of the first characteristic peak to the peak area A2 of the second characteristic peak in the particle size distribution curve of the matrix material and the amount of free lithium converter added.
[0102] The preparation method of the present application is described in detail below with reference to the examples:
[0103] In some embodiments, the free lithium ion conversion agent contains N, wherein N includes at least one of W, B, Mo, F, S, V, P, and Cl elements.
[0104] In some embodiments, the free lithium ion conversion agent includes at least one of KAl(SO4)2, NH4HSO4, MgCl2, NH4Cl, CaF2, NH4HWO4, NH4MoO4, NH4HBO3, NH4HF2, NaVO3, NH4VO3, (NH4)3PO4, (NH4)2HPO4, and Ca(H2PO4)2. In this embodiment, after the free lithium ion conversion agent is added to the aqueous solution of the matrix material, the cations or cationic groups and the anions or anionic groups are hydrolyzed, wherein the anions or anionic groups are combined with the lithium ions in the residual lithium (lithium hydroxide, lithium carbonate) on the surface of the matrix material to form lithium salts (LiOH) in situ on the surface of the matrix material. x N y O z ) molecular layer, such as Li2WO4, Li3BO3, LiMoO4, LiVO3, Li2SO4, Li3PO4 molecular layer, etc. x N y O z The compounds are usually structurally stable and can effectively improve the cycle performance of the positive electrode materials, while the cations or cationic groups will react with the OH- and CO3 in the residual lithium 2- Oxidation-reduction reaction occurs, generating H20 and CO2 which are discharged, or transferred from the surface of the substrate material into deionized water. In this embodiment, the free lithium ion converter not only reduces the free lithium on the surface of the positive electrode material, but also reduces the structural damage caused by water washing, thereby improving the cycle performance of the positive electrode material.
[0105] The conversion rate of the Li2SO4 protective layer is lower than that of the Li3PO4 protective layer. Substituting it into the formula, the θ value is 13.44. The Li3PO4 protective layer can more effectively reduce the structural damage and side reactions during the cycle.
[0106] In some embodiments, during the sintering process of the precursor, the sintering temperature is 250°C to 500°C, and specifically can be 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or any value therebetween.
[0107] In some embodiments, during the sintering process of the precursor, the sintering time is 6 hours to 12 hours, and specifically can be 6 hours, 8 hours, 10 hours, 12 hours, or any value therebetween.
[0108] In some embodiments, in the aqueous solution of the matrix material, the mass of the deionized water is 15% to 30% of the mass of the matrix material, and specifically can be 15%, 20%, 25%, 30% or any value therebetween.
[0109] In some embodiments, the step of preparing the aqueous solution of the matrix material includes: mixing the matrix material with deionized water and stirring them evenly. During the preparation of the aqueous solution of the matrix material, the deionized water will wash away some of the residual lithium on the surface of the matrix material, and by uniformly dispersing the matrix material in the deionized water, the activity of the residual lithium on the surface of the matrix material can be enhanced, which is conducive to the modification of the matrix material by the free lithium ion conversion agent in the later stage.
[0110] In some embodiments, the stirring speed is 20 Hz to 50 Hz, specifically 20 Hz, 30 Hz, 40 Hz, 50 Hz or any value therebetween. By controlling the stirring speed within the above range, it is helpful to control the P value within an appropriate range; if the stirring speed is too high, it is easy to cause the loss of small particles, which will destroy the stability of the material and make the P value too high.
[0111] In some embodiments, the stirring time is 20 min to 40 min, specifically 20 min, 30 min, 40 min or any value therebetween. By controlling the stirring time within the above range, it is helpful to control the P value within an appropriate range; if the stirring time is too long, it is easy to cause the loss of small particles, which will destroy the stability of the material and make the P value too high.
[0112] In some embodiments, the matrix material is a composite oxide including Li, Ni, Co, and Mn elements.
[0113] In some embodiments, the step of preparing the matrix material includes: preparing a mixture material including a ternary precursor and a lithium source, and sintering the mixture material under an oxygen atmosphere to obtain the matrix material.
[0114] In some embodiments, in the step of preparing the matrix material, the oxygen flow rate of the oxygen atmosphere is 200 m / s. 3 / h~450m 3 / h, specifically 200m 3 / h、250m 3 / h、300m 3 / h、350m 3 / h、400m 3 / h、450m 3 By controlling the oxygen flow rate of the oxygen atmosphere within the above range, it is beneficial to control the P value within an appropriate range.
[0115] In some embodiments, in the step of preparing the base material, the furnace pressure of sintering is 3Pa to 25Pa, specifically 3Pa, 6Pa, 9Pa, 12Pa, 15Pa, 18Pa, 21Pa, 23Pa, 25Pa or any value therebetween. By controlling the furnace pressure of sintering within the above range, it is helpful to control the P value within a suitable range.
[0116] In some embodiments, in the preparation step of the base material, sintering includes a constant temperature stage, and the sintering temperature in the constant temperature stage is 600° C.-800° C., specifically 600° C., 700° C., 800° C. or any value therebetween. By controlling the sintering temperature in the constant temperature stage within the above range, it is helpful to control the P value within an appropriate range.
[0117] In some embodiments, the sintering time in the constant temperature stage is 8 hours to 15 hours, specifically 8 hours, 10 hours, 12 hours, 15 hours or any value therebetween. By controlling the sintering time in the constant temperature stage within the above range, it is helpful to control the P value within an appropriate range.
[0118] In some embodiments, in the preparation step of the matrix material, sintering also includes a heating stage, and the heating rate of the heating stage is 2°C / min to 5°C / min, specifically 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value therebetween; during the sintering process, the sintering temperature is increased to 600°C-800°C at a heating rate of 2°C / min to 5°C, and then a constant temperature stage is performed for constant temperature sintering.
[0119] In some embodiments, the chemical formula of the ternary precursor is Ni a Co b Mn c (OH)2, 0.8≤a≤0.98, 0.01≤b≤0.2, 0.01≤c≤0.2.
[0120] In some embodiments, the ternary precursor includes first particles (large particles) and second particles (small particles) of different particle sizes, the chemical expressions of the first particles and the second particles may be the same or different, and the particle size D50 of the first particles is 12 μm-18 μm, specifically 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or any value therebetween. The particle size of the first particle will affect the specific surface area of the positive electrode material. The smaller the particle size, the larger the specific surface area, and the positive electrode material is more likely to react with water and carbon dioxide in the air, which will lead to an increase in residual lithium; by controlling the particle size D50 of the first particle within the above range, it is beneficial to control the amount of residual lithium on the surface of the positive electrode material within a preferred range.
[0121] In some embodiments, the particle size D50 of the second particles is 2μm-5μm, specifically 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or any value therebetween. Similarly, the particle size of the second particles will affect the specific surface area of the positive electrode material. The smaller the particle size, the larger the specific surface area, and the positive electrode material is more likely to react with water and carbon dioxide in the air, which will lead to an increase in residual lithium. By controlling the particle size D50 of the second particles within the above range, it is beneficial to control the amount of residual lithium on the surface of the positive electrode material within a preferred range.
[0122] In some embodiments, the particle size D50 of the first particle is 12 μm-18 μm, and the particle size D50 of the second particle is 2 μm-5 μm. By controlling the particle sizes of the first particle and the second particle simultaneously within the above range, it is beneficial to improve the compatibility of the first particle and the second particle, improve the compaction density and structural stability of the positive electrode material, and thus further improve the conductivity and cycle performance of the positive electrode material.
[0123] In some embodiments, the mass ratio of the first particles to the second particles is 1:(1-5), specifically 1:1, 1:2, 1:3, 1:4, 1:5 or any value therebetween. By controlling the mass ratio of the first particles to the second particles within the above range, the cycle performance of the positive electrode material is further improved.
[0124] In some embodiments, the lithium source includes at least one of hydrated lithium hydroxide, lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, and lithium oxalate.
[0125] In some embodiments, the molar ratio of the Li element in the lithium source to the ternary precursor is 0.95 to 1.25, specifically 0.95, 1, 1.05, 1.1, 1.15, 1.2, 1.25 or any value therebetween. By controlling the molar ratio of the Li element in the lithium source to the ternary precursor within the above range, it is beneficial to improve the binding force between the lithium element and the precursor, stabilize the crystal structure, release capacity and cycle performance.
[0126] In some embodiments, the matrix material is doped with an M element, and the M element includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb.
[0127] In some embodiments, the mixed material also includes an M dopant; during the preparation of the matrix material, the M element in the M dopant will construct an ion conductor transport layer together with other metal elements in the ternary precursor, which is beneficial to improving the electrical conductivity of the positive electrode material.
[0128] In some embodiments, the M dopant includes at least one of Sr(OH)2, SrO, TiO2, Al2O3, Al(OH)3, ZrO2, Zr(OH)4, Ba(OH)2, BaO, MgO, Mg(OH)2, Nb2O5, Nb2O3, WO3 and CaWO4.
[0129] In some embodiments, the mass of the M dopant is 0.1% to 0.55% of the mass of the ternary precursor, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.55% or any value therebetween, preferably, the mass of the M dopant is 0.2% to 0.4% of the mass of the ternary precursor, specifically 0.2%, 0.3%, 0.4% or any value therebetween. By controlling the amount of the M dopant added within an appropriate range, it is beneficial to improve the conductivity of the positive electrode material while taking into account other properties such as the capacity and cycle performance of the positive electrode material.
[0130] In some embodiments, the modification treatment is carried out in an ultrasonic environment. Ultrasonic waves have good directionality and are easy to obtain concentrated sound energy. During the modification treatment, energy for the free lithium converter to participate in the reaction is provided by ultrasonic induction, forming a highly reactive environment; at the same time, the aggregation of molecules is induced by ultrasonic cavitation, the diffusion of reactants and the formation of coating layers are accelerated, and uniform mixing between the reactants is achieved. Under ultrasonic induction, the distribution uniformity of the elements is significantly improved, and the lithium salt compounds generated by the reaction will directional build a structural protective layer on the surface of the positive electrode material, thereby protecting the main structure of the positive electrode material from loss, and effectively improving the cycle performance of the positive electrode material.
[0131] In some embodiments, the frequency of the ultrasound is 20kHz to 50kHz, specifically 20kHz, 30kHz, 40kHz, 50kHz or any value therebetween. The frequency of the ultrasound will affect the conversion rate of residual lithium on the surface of the positive electrode material and the structural stability of the coating layer on the surface of the positive electrode material, thereby affecting the cycle performance of the positive electrode material. By controlling the frequency of the ultrasound within the above range, it is beneficial to control the P value and the content of free lithium in the positive electrode material within an appropriate range, thereby facilitating the improvement of the cycle performance of the positive electrode material.
[0132] In some embodiments, the ultrasonic time is 20 min-40 min, specifically 20 min, 30 min, 40 min or any value therebetween. Similarly, the ultrasonic time of the ultrasonic wave will also affect the conversion rate of residual lithium on the surface of the positive electrode material and the structural stability of the coating layer on the surface of the positive electrode material, thereby affecting the cycle performance of the positive electrode material. By controlling the ultrasonic time of the ultrasonic wave within a suitable range, it is beneficial to control the P value and the content of free lithium in the positive electrode material within a suitable range, thereby facilitating the improvement of the cycle performance of the positive electrode material.
[0133] In some embodiments, the solid-liquid separation includes subjecting the modified mixture to a filter press treatment, wherein the extrusion pressure of the filter press is 0.2 MPa-0.5 MPa, specifically 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween.
[0134] In some embodiments, the filtration time is 10 min-30 min, specifically 10 min, 20 min, 30 min or any value therebetween.
[0135] In some embodiments, after the filter press treatment, the solid-liquid separation further includes drying the modified mixture in succession, and the drying temperature is 80-170°C, specifically 80°C, 100°C, 120, 140°C, 160°C, 170°C or any value therebetween.
[0136] In some embodiments, the drying time is 1 h to 3 h, specifically 1 h, 2 h, 3 h or any value therebetween.
[0137] The free lithium stability coefficient of the positive electrode material prepared by the preparation method of the present application is L, L = (L1-L2) / L1, and the test method of L1 and L2 is: take 5g of positive electrode material and disperse it in 100ml of deionized water, stir it magnetically for t min, and filter the filtrate to determine the free lithium content; when t = 60, the mass content of free lithium in the positive electrode material is measured to be L1%, and when t = 10, the mass content of free lithium in the positive electrode material is measured to be L2%.
[0138] In some embodiments, 10≤P*L≤25. The applicant also found in the research process that there is a certain correlation between the free lithium stability coefficient L and the peak area ratio P. Changing the peak area A2 or A1 means a change in the grain boundary at the microscopic level, and a change in the contact area from a macroscopic perspective, which will cause the amount of residual alkali generated by the positive electrode material reacting with carbon dioxide and water in the air to change, thereby changing the conversion efficiency of free lithium on the surface of the positive electrode material, and then affecting the structural stability of the positive electrode material, and the structural stability of the positive electrode material is a key factor affecting its cycle performance. Therefore, in this embodiment, the present application incorporates the free lithium stability coefficient L into the calculation formula of the positive electrode material cycle performance. When 10≤θ=P*L≤25, the positive electrode material has excellent cycle performance and can meet application requirements. Since the parameters A1, A2, L1 and L2 involved in the calculation formula of θ can be quickly measured, in the evaluation of the cycle performance of the positive electrode material, the A1, A2, L1 and L2 values of the positive electrode material can be tested and the cycle performance measurement parameter θ can be calculated to achieve a rapid evaluation of the cycle performance of the positive electrode material, which can greatly shorten the test cycle and test costs.
[0139] In some embodiments, 0.25≤L=(L1-L2) / L1≤0.85. L is the free lithium stability coefficient of the positive electrode material, which is used to measure the stability of the free lithium on the surface of the positive electrode material. If L is too high, the free lithium content on the surface of the positive electrode material is high, and there may be unstable lithium ions inside the positive electrode material, which are easy to dissolve, and the stability of the structural functional layer on the surface of the positive electrode material is poor; if L is too low, it means that the lattice lithium in the positive electrode material has suffered a certain loss, causing some stable Li to dissolve, resulting in different test conditions. The measured free lithium content does not change much. In this case, the capacity cycle retention rate of the positive electrode material is easily affected. By controlling a series of reaction conditions during the modification process, it is beneficial to limit L within an appropriate range, improve the structural stability of the positive electrode material, and greatly improve the cycle performance of the positive electrode material.
[0140] In some embodiments, L1 is 0.15% to 0.45%, specifically 0.15%, 0.25%, 0.35%, 0.45% or any value therebetween.
[0141] In some embodiments, L2 is 0.02% to 0.16%, specifically 0.02%, 0.08%, 0.12%, 0.16% or any value therebetween.
[0142] In some embodiments, A1 is 4-25, specifically 4, 8, 12, 16, 20, 25 or any value therebetween.
[0143] In some embodiments, A2 is 150-250, specifically 150, 200, 250 or any value therebetween.
[0144] In a third aspect, the present application further proposes a lithium-ion battery, which includes the positive electrode material as above, or includes the positive electrode material prepared by the above preparation method.
[0145] The above is only a preferred implementation mode of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
[0146] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments, and can be appropriately modified and implemented within the scope of the unchanged main rights.
[0147] Example 1
[0148] (1) Take the large particle precursor Ni a Co b Mn c (OH)2 (i.e., the first particle), wherein the molar ratio of Ni, Co, and Mn is 88.5:9.0:2.5, and the particle size D50 is 16 μm; and, taking a small particle precursor NiaCobMnc(OH)2 (i.e., the second particle), wherein the molar ratio of Ni, Co, and Mn is 88.5:9.0:2.5, and the particle size D50 is 3 μm; the large particle precursor and the small particle precursor are mixed in a weight ratio of 1:4 to obtain a mixed precursor Ni 88.5 Co9Mn 2.5 (OH)2.
[0149] (2) The obtained precursor Ni 88.5 Co9Mn 2.5 (OH)2 and LiOH are mixed with dopants Al(OH)3, TiO2 and Sr(OH)2, and ground into powder. 88.5 Co9Mn 2.5 The molar ratio of (OH)2 to LiOH is 1.02, and the precursor Ni 88.5 Co9Mn 2.5 The mass of Al(OH)2 is 100wt%, the content of Al(OH)3 is 0.2wt%, the content of TiO2 is 0.1wt%, and the content of Sr(OH)2 is 0.2wt%; the mixed material is then heated to 750°C at a rate of 2°C / min under an oxygen atmosphere, then sintered at a constant temperature for 10 hours, cooled, sieved and crushed to obtain a matrix material.
[0150] (3) Weigh 200 g of the obtained matrix material and put it into a reactor, add deionized water in an amount of 25 wt% of the weight of the matrix material, set the stirring speed to 30 Hz, and stir for 30 min; after the stirring is completed, put the reactor into an ultrasonic vibrator, set the transducer frequency to 35 kHz, add (NH4)2HPO4 with a matrix material content of 0.8 wt%, and ultrasonically vibrate for 30 min.
[0151] (4) The material obtained in (3) is placed in a filter press for filtration at a pressure of 0.4 MPa for 20 minutes. After filtration, the material is placed in an oven for drying at a temperature of 150°C for 120 minutes. Then, the obtained material is further sintered at a temperature of 400°C for 8 hours to obtain a positive electrode material.
[0152] Combination Figure 2 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 1, and the calculated values of L, P and θ are shown in Table 1.
[0153] Example 2
[0154] The difference from Example 1 is that:
[0155] The D50 of the large particle precursor was changed to 12μm, and the D50 of the small particle precursor was changed to 2.5μm.
[0156] Combination Figure 3 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 2, and the calculated values of L, P and θ are shown in Table 1.
[0157] Example 3
[0158] The difference from Example 1 is that:
[0159] The D50 of the large particle precursor was changed to 18μm, and the D50 of the small particle precursor was changed to 2.5μm.
[0160] Combination Figure 4 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 3, and the calculated values of L, P and θ are shown in Table 1.
[0161] Example 4
[0162] The difference from Example 3 is that:
[0163] The constant temperature sintering temperature in step (2) is adjusted to 700°C.
[0164] Combination Figure 5 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 4, and the calculated values of L, P and θ are shown in Table 1.
[0165] Example 5
[0166] The difference from Example 3 is that:
[0167] The dopants were replaced with 0.4 wt% Al(OH)3, 0.2 wt% TiO2, 0.2 wt% Sr(OH)2 and 0.3 wt% Ba(OH)2.
[0168] Combination Figure 6 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 5, and the calculated values of L, P and θ are shown in Table 1.
[0169] Example 6
[0170] The difference from Example 5 is that:
[0171] In step (3), (NH4)3PO4 with a matrix material content of 1.2 wt% is added.
[0172] Combination Figure 7 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 6, and the calculated values of L, P and θ are shown in Table 1.
[0173] Example 7
[0174] The difference from Example 6 is that:
[0175] The free lithium ion conversion agent was changed to NH4HSO4.
[0176] Combination Figure 8 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 7, and the calculated values of L, P and θ are shown in Table 1.
[0177] Example 8
[0178] The difference from Example 5 is that:
[0179] The free lithium ion converter was changed to 0.4 wt % (NH4)2HPO4 and 0.4 wt % NH4HSO4.
[0180] Combination Fig. 9 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 8, and the calculated values of L, P and θ are shown in Table 1.
[0181] Example 9
[0182] The difference from Example 1 is that:
[0183] In step (3), (NH4)2HPO4 with a matrix material content of 0.6 wt% is added.
[0184] Combination Fig.10 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 9, and the calculated values of L, P and θ are shown in Table 1.
[0185] Example 10
[0186] The difference from Example 6 is that:
[0187] In step (3), the frequency of the transducer is 5 kHz.
[0188] Combination Fig.11 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 10, and the calculated values of L, P and θ are shown in Table 1.
[0189] Embodiment 11
[0190] The difference from Example 6 is that:
[0191] The stirring time in step (3) is 40 min.
[0192] Combination Fig.12 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Example 11, and the calculated values of L, P and θ are shown in Table 1.
[0193] Comparative Example 1
[0194] The difference from Example 5 is that:
[0195] The free lithium ion conversion agent was changed to 0.4 wt% (NH4)2HPO4.
[0196] Combination Fig.13 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 1, and the calculated values of L, P and θ are shown in Table 1.
[0197] Comparative Example 2
[0198] The difference from Example 5 is that:
[0199] The free lithium ion converter was changed to 1.3 wt% (NH4)2HPO4.
[0200] Combination Fig.14 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 2, and the calculated values of L, P and θ are shown in Table 1.
[0201] Comparative Example 3
[0202] The difference from Example 1 is that:
[0203] The mixing mass ratio of large particle precursor to small particle precursor was changed to 3:2.
[0204] Combination Fig.15 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 3, and the calculated values of L, P and θ are shown in Table 1.
[0205] Comparative Example 4
[0206] The difference from Example 1 is that:
[0207] The mixing mass ratio of large particle precursor to small particle precursor was changed to 1:6.
[0208] Combination Fig.16 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 4, and the calculated values of L, P and θ are shown in Table 1.
[0209] Comparative Example 5
[0210] The difference from Example 1 is that:
[0211] The D50 of the large particle precursor was changed to 22μm.
[0212] Combination Fig.17 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 5, and the calculated values of L, P and θ are shown in Table 1.
[0213] Comparative Example 6
[0214] The difference from Example 1 is that:
[0215] The D50 of the large particle precursor was changed to 8μm.
[0216] Combination Fig.18 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 6, and the calculated values of L, P and θ are shown in Table 1.
[0217] Comparative Example 7
[0218] The difference from Example 1 is that:
[0219] The D50 of the small particle precursor was changed to 8μm.
[0220] Combination Fig.19 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 7, and the calculated values of L, P and θ are shown in Table 1.
[0221] Comparative Example 8
[0222] The difference from Example 1 is that:
[0223] The D50 of the small particle precursor was changed to 1μm.
[0224] Combination Fig. 20 The specific test results of the peak area A1 of the first characteristic peak, the peak area A2 of the second characteristic peak, the free lithium content L1 and the free lithium content L2 of the positive electrode material prepared in Comparative Example 8, and the calculated values of L, P and θ are shown in Table 1.
[0225] The performance tests were performed on the samples prepared in the above Examples 1-11 and Comparative Examples 1-8, and the test methods were as follows:
[0226] 1. Calculation of the peak area of the first characteristic peak and the second characteristic peak:
[0227] The raw data obtained from the particle size distribution test is imported into origin to draw the image. Through the integrate command, the starting point x1 and the end point x2 of the first characteristic peak are selected to obtain the peak area A1 with y=0 as the base. The peak area A2 of the second characteristic peak is obtained by the same method.
[0228] 2. Residual alkali test:
[0229] 5 g of positive electrode material was dispersed in 100 ml of deionized water, and residual carbonate and hydroxide were dissolved by magnetic stirring for a certain period of time; the filtrate was obtained after suction filtration, and hydrochloric acid solution was added to an automatic potentiometric titrator, and titration was performed in an equivalent dropwise manner, and the contents of carbonate and hydroxide in the positive electrode material were calculated according to the situation of the breakthrough point and the degree of consumption of the hydrochloric acid solution; when the stirring time was 60 min, the mass content of free lithium in the sample was measured to be L1, and when the stirring time was 10 min, the mass content of free lithium in the sample was measured to be L2.
[0230] 3. Particle size test:
[0231] The particle size distribution of the positive electrode material particles was obtained by using a British Malvern Mastersizer 3000 laser particle size analyzer and utilizing the light intensity distribution of laser diffraction.
[0232] 4. Morphology test
[0233] The surface morphology of the material was characterized by a Hitachi Regulus 8100 field emission scanning electron microscope with an accelerating voltage of 1 Kv.
[0234] 5. Power-off performance test:
[0235] 0.8g of positive electrode material, 0.1g of conductive carbon black, and 0.1g of polyvinylidene fluoride were put into a ball mill, and 15ml of N-methylpyrrolidone was added. The mixture was ball milled to form a uniform slurry, and then evenly coated on aluminum foil and vacuum dried at 110°C for 12h to obtain a positive electrode. The dried electrode was cut into 15mm round pieces, and assembled and sealed in a glove box according to the positive electrode shell, electrode, electrolyte (EC / DMC / EMC volume ratio 1:1:1, LiPF6 concentration of 1mol / L), diaphragm (Celgard PP / PE / PP three-layer composite film), lithium sheet, electrolyte, nickel foam, and negative electrode shell to obtain a button battery, which was left to stand for 24h. The obtained battery was then placed in a thermostat for testing. The battery was discharged to 2.0V at a current density of 1C, and then charged to 4.2V at a current density of 1C after standing for 2 minutes. The above steps were repeated for 50 cycles to obtain the cycle retention rate. The battery was fully charged to 4.2V and maintained for 1 hour, and then the battery was adjusted to 100% SOC using a current density of 1C, and stood for 30 minutes. The voltage V0 at this time was recorded, and the discharge current ts of 1C was used to record the voltage V1 at ts. The DC resistance of the 50th week was calculated based on (V0-V1) / It.
[0236] The LAND battery testing system was used to conduct discharge capacity (0.1C / 0.5C / 1C) and first-cycle charge and discharge efficiency performance tests at 25°C and 3.0V to 4.3V. The reference capacity was set to 200mA / g, and 1C corresponded to a current density of 200mA / g.
[0237] 6. Conductivity test:
[0238] Use a resistivity tester (Suzhou Jingge Electronics ST-2255A), take 5g of powder sample, use an electronic press to press it to 5000kg±2kg, and maintain it for 15-25s. Place the sample between the electrodes of the tester, the sample height is h (cm), the voltage at both ends is U, the current is I, and the area after the powder is pressed is S = 3.14cm 2 The electronic conductivity of the powder is calculated according to the formula σ=h / (S*R) / 1000.
[0239] 7. Compaction test:
[0240] The compaction density tester of the positive electrode material was used to test the compaction performance of the positive electrode material. 1g of the positive electrode material was processed and compacted under a pressure of 3t for 30s to obtain the compaction data of the material. The compaction density was > 3g / cm 3 .
[0241] 8. Specific surface area test:
[0242] The specific surface area of the material was calculated using the American TriStar II specific surface and pore analyzer by nitrogen adsorption and the BET method.
[0243] 9. XRD test:
[0244] The crystal structure of the positive electrode active material can be determined by an X-ray powder diffractometer, for example, a Brucker D8A_A25 X-ray diffractometer from BruckerAxS of Germany, with CuKα rays as the radiation source, a ray wavelength scanning 2θ angle range of 10° to 90°, and a scanning rate of 4° / min.
[0245] The physicochemical parameter test results of the samples prepared in Examples 1-11 and Comparative Examples 1-8 are shown in Table 1 below:
[0246]
[0247]
[0248] The test results of the electrical performance of the samples prepared in Examples 1-11 and Comparative Examples 1-8 are shown in Table 2 below:
[0249]
[0250] The test results of the conductivity, compacted density and specific surface area obtained in Examples 1-11 and Comparative Examples 1-8 are shown in Table 3 below:
[0251] sample Conductivity (S / cm) <![CDATA[Compaction density (g / cm 3 )]]> <![CDATA[Specific surface area (m 2 / g)]]> Example 1 0.058 3.51 0.62 Example 2 0.037 3.28 0.51 Example 3 0.052 3.39 0.59 Example 4 0.041 2.36 0.52 Example 5 0.068 3.55 0.65 Example 6 0.075 3.62 0.72 Example 7 0.050 3.40 0.55 Example 8 0.046 3.38 0.54 Example 9 0.052 3.40 0.52 Example 10 0.059 3.42 0.61 Embodiment 11 0.061 3.42 0.63 Comparative Example 1 0.022 2.95 0.41 Comparative Example 2 0.023 3.11 0.39 Comparative Example 3 0.036 2.18 0.35 Comparative Example 4 0.018 3.15 0.42 Comparative Example 5 0.041 2.15 0.35 Comparative Example 6 0.037 2.07 0.37 Comparative Example 7 0.025 3.12 0.43 Comparative Example 8 0.023 3.56 0.46
[0252] Analyze the above Tables 1, 2 and 3:
[0253] By comparing Examples 1-11 with Comparative Examples 1-8, it can be concluded that when the positive electrode material satisfies the relationship: 10≤θ=P*L≤25, it has relatively excellent cycle performance and conductivity; and when θ is in the range of 10-20, the larger the θ value, the higher the cycle retention rate and conductivity of the positive electrode material, among which, when θ is in the range of 18-20, the compaction density and specific surface area of the positive electrode material have obvious advantages; when θ is in the range of 20-25, the larger the θ value, the smaller the cycle retention rate and conductivity of the positive electrode material; when θ is not in the above range, the cycle performance and conductivity of the positive electrode material are relatively poor, and the application is greatly restricted.
[0254] Among them, by comparing Comparative Examples 1-2 with Example 5, it can be concluded that both too high and too low content of free lithium ion converter are not conducive to forming a stable protective layer on the surface of the positive electrode material. Too high content will lead to uneven coating layer formed on the surface of the positive electrode material, and too low content will not be able to effectively block the occurrence of side reactions. Both will lead to a decrease in material conductivity and a decrease in cycle performance.
[0255] By comparing Example 1 with Comparative Examples 3-8, it can be analyzed that: the role of large particles in the positive electrode material is mainly reflected in increasing the capacity of the material, but cracks and pores are prone to appear during the cycle, affecting the cycle performance; small particles have better physical stability, can stabilize the material structure, and prevent the positive electrode material from breaking particles during the cycle, thereby improving the cycle stability and safety performance; the appropriate ratio of large and small particles in the positive electrode material is critical to improving its performance: appropriate particle size distribution and particle matching can enable a better solid / solid interface between the active substance and the electrolyte, thereby accelerating the transmission speed of lithium ions. At the same time, the appropriate combination of large and small particles can increase the compaction density of the material, improve the mass of the active substance per unit volume of the material, and is conducive to the release of the electrochemical properties of the material. In detail:
[0256] By comparing Comparative Examples 3, 5, and 6 with Example 1, it can be concluded that: in the positive electrode material, if the specific gravity of the large-particle precursor is too large or the D50 is too large, the stability and safety of the positive electrode material will decrease, and the compaction density and capacity of the positive electrode material will both decrease. At the same time, too many large particles will cause a significant decrease in the compaction density of the material; if the D50 of the large-particle precursor is too small, the lithium ion transmission speed will decrease, and the conductivity and capacity of the material will decrease.
[0257] By comparing Comparative Examples 4, 7, and 8 with Example 1, it can be concluded that: in the positive electrode material, the small particle precursor has a large specific gravity or D50 is large, and it is easy to agglomerate, which causes the compaction density and specific surface area of the material to decrease, resulting in a decrease in the capacity of the material, and affects the structural stability of the material, thereby reducing the cycle of the positive electrode material; if the specific gravity D50 of the small particle precursor is small, it will cause the finished positive electrode material to be prone to micropowder, affecting the electrochemical performance. At the same time, the micropowder will also affect the uniformity of the coating layer, resulting in a decrease in the electrical conductivity of the material.
[0258] In addition, through a detailed analysis of Examples 1-11, it can be concluded that: in the preparation process of the positive electrode material, the A1 value, A2 value, L1 value, and L2 value of the finished positive electrode material can be adjusted by regulating the particle size of the precursor and the matching ratio of the particles, the sintering temperature, the type of dopant, the type and content of the free lithium ion converter, the ultrasonic intensity, and the water washing and stirring time, so that the peak area ratio P value and the free lithium stability coefficient L of the prepared positive electrode material are within an appropriate range.
[0259] In detail, compared with Example 1, the particle size D50 of the large and small particle precursors of Example 2 is reduced, the A1 peak area is reduced, and the A2 peak area is reduced; that is, the large and small particle precursors are all smaller, resulting in an increase in the specific surface, causing the material to react more easily with water and carbon dioxide in the air, thereby increasing the residual lithium on the surface of the material. Therefore, the θ value calculated for the finished positive electrode material in Example 2 is 21.18, its A1 is not within the specified range, and its cycle performance is reduced compared with Example 1.
[0260] Compared with Example 1, A1 of Example 3 is reduced, A2 is increased, and the overall A2 / A1 is increased. The reason is that the particle size of small particles is reduced, and the particle size of large particles is increased. Under this condition, the particle size adaptability of large particles and small particles is better: smaller particles reduce the volume expansion of the material during the charge and discharge process, making the structure of the material more stable, and the appropriate increase in the particle size of large particles also reduces the number of grain boundaries that hinder the diffusion of lithium ions, Li + The transmission is faster, the conductivity is increased, and while maintaining a similar stability coefficient of free lithium, the θ value increases to 16.16, and the material's cycle performance is improved.
[0261] Compared with Example 3, the constant temperature sintering temperature of Example 4 is reduced, L1 increases, and the cycle performance deteriorates. This is because the temperature conditions required for grain growth of large particles and small particles are different, and it is necessary to determine the appropriate sintering temperature. Compared with Experimental Example 3, Example 4 reduces the sintering temperature, which slows down the growth rate of the material grain size, makes the grain size smaller, and reduces the lithium ion transmission path. At the same time, there is also the problem of insufficient sintering temperature required for lithium to enter the lattice. Therefore, relative to Example 3, L1 of Example 4 increases, does not meet the range of 0.15% ≤ L1 ≤ 0.45%, and the cycle performance of the finished positive electrode material deteriorates.
[0262] Compared with Example 3, Example 5 uses co-doping of four metal ions of Al / Ti / Sr / Ba, which can effectively stabilize the crystal structure of the material, improve the chemical stability of TM-O-Li, and improve the Li / Ni mixing situation, thereby improving the conductivity and cycle stability of the finished positive electrode material.
[0263] Compared with Example 5, Example 6 and Example 9 adjust the content of the free lithium ion converter. The content of the free lithium ion converter is appropriately increased, which is beneficial to further improve the cycle stability of the positive electrode material. The reason is that the increase in the content of the free lithium ion converter further improves the conversion efficiency of the free lithium in the positive electrode material, and the excess residual alkali on the surface of the material fully reacts with the free lithium converter, so that the material obtains more effective coating layers, that is, the stability of the coating layer formed on the surface of the material is improved, which can reduce the generation of pores and cracks, and can more effectively reduce the side reactions of the active substance and the electrolyte.
[0264] Compared with Example 1, the free lithium ion conversion agent in Example 7 is changed to NH4HSO4, and the cycle performance of the finished positive electrode material is reduced. According to the test results, it is explained that NH4HSO4 has a worse conversion of residual alkali and is more difficult to form a stable structural protective layer. The conversion rate of the Li2SO4 coating layer is lower than that of the Li3PO4 coating layer, and the Li3PO4 coating layer can more effectively reduce the occurrence of structural damage and side reactions during the cycle.
[0265] Compared with Example 5, Example 8 simultaneously mixed and used free lithium ion converters (NH4)2HPO4 and NH4HSO4, and the cycle performance of the finished positive electrode material was reduced. The reason is that the Li2SO4 coating layer and the Li3PO4 coating layer cannot be formed evenly, thereby affecting the structural stability of the surface coating layer of the finished positive electrode material.
[0266] Compared with Example 6, Example 10 increases the ultrasonic intensity to 50kHZ, and the cycle performance of the finished positive electrode material is reduced. The reason is that too high ultrasonic energy will cause the coating layer to be unstable and in a metastable state, which is not conducive to improving the structural stability of the coating layer.
[0267] Compared with Example 5, Example 11 increases the pre-water washing stirring time in the reactor to 40 minutes, and the cycle performance of the finished positive electrode material is reduced. The reason is that: too high a rotation speed easily leads to the loss of small particles, which leads to a high A2 / A1, destroys the material stability, and reduces the cycle performance of the finished positive electrode material.
Claims
1. A positive electrode material, characterized in that: The positive electrode material is a nickel-cobalt-lithium oxide composite oxide; The particle size distribution curve of the positive electrode material has a first characteristic peak and a second characteristic peak, the peak area of the first characteristic peak is A1, the peak area of the second characteristic peak is A2, P= A2 / A1, P is the ratio of the peak area of the volume density occupied by large particles to the peak area of the volume density occupied by small particles in the particle size distribution curve of the positive electrode material; The free lithium stability coefficient of the positive electrode material is L, L=(L1-L2) / L1, and the test method of L1 and L2 is: take 5g of positive electrode material and disperse it in 100ml of deionized water, stir it magnetically for t min, and filter the filtrate to determine the free lithium content; when t=60, the mass content of free lithium in the positive electrode material is measured to be L1, and when t=10, the mass content of free lithium in the positive electrode material is measured to be L2; The positive electrode material satisfies the following relationship: , where 0.25≤L≤0.
85.
2. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following characteristics: (1) The general chemical formula of the positive electrode material is: LiNi a Co b Mn c M d N e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, and the M includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb, and the N includes at least one of W, B, Mo, F, S, V, P, and Cl; (2) The positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material, wherein the base material is a composite oxide including Ni, Co, Mn and M elements, and the M element includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg and Nb.
3. The positive electrode material according to claim 1, characterized in that The positive electrode material comprises a base material and a coating layer located on at least a portion of the surface of the base material, wherein the coating layer comprises a lithium salt, and the chemical formula of the lithium salt is Li x N y O z , wherein x, y, z>0, and N includes at least one of W, B, Mo, F, S, V, P and Cl.
4. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following characteristics: (1)0.15 %≤L1≤0.45 %; (2)0.02 %≤L2≤0.16 %; (3)8≤P≤50; (4)4≤A1≤25; (5)150≤A2≤250; (6) The conductivity of the positive electrode material is 0.025 S / cm~0.080 S / cm; (7) The compaction density of the positive electrode material is 3.10 g / cm 3 ~3.65 g / cm 3 ; (8) The specific surface area of the positive electrode material is 0.4 m 2 / g ~0.8 m 2 / g.
5. A method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: Adding a free lithium ion conversion agent to an aqueous solution of a base material for modification treatment, wherein the free lithium ion conversion agent is used to absorb residual lithium in the base material, and the amount of the free lithium ion conversion agent added is 0.6 wt %-1.2 wt % based on the mass of the base material as 100 wt %, to obtain a modified mixture, and performing solid-liquid separation on the modified mixture to obtain a precursor; wherein the base material is a nickel cobalt lithium oxide composite oxide; The precursor is sintered to obtain a positive electrode material.
6. The preparation method according to claim 5, characterized in that: Includes at least one of the following features: (1) In the aqueous solution of the matrix material, the mass of deionized water is 15% to 30% of the mass of the matrix material; (2) The matrix material is a composite oxide comprising Li, Ni, Co, Mn and M elements, wherein the M element comprises at least one of Sr, Ti, Al, Zr, W, Ba, Mg and Nb; (3) The preparation step of the matrix material includes: preparing a mixture including a ternary precursor, a lithium source and an M dopant, and sintering the mixture in an oxygen atmosphere to obtain the matrix material; wherein the M includes at least one of Sr, Ti, Al, Zr, W, Ba, Mg, and Nb.
7. The preparation method according to claim 6, characterized in that: Also includes at least one of the following features: (1) The chemical formula of the ternary precursor is Ni a Co b Mn c (OH)2, 0.8≤a≤0.98, 0.01≤b≤0.2, 0.01≤c≤0.2; (2) The M dopant includes at least one of Sr(OH)2, SrO, TiO2, Al2O3, Al(OH)3, ZrO2, Zr(OH)4, Ba(OH)2, BaO, MgO, Mg(OH)2, Nb2O5, Nb2O3, WO3 and CaWO4; (3) The mass of the M dopant is 0.1% to 0.55% of the mass of the ternary precursor; (4) The ternary precursor comprises first particles and second particles of different particle sizes, and the particle size D50 of the first particles is 12 μm-18 μm; (5) The ternary precursor comprises first particles and second particles of different particle sizes, and the particle size D50 of the second particles is 2 μm-5 μm; (6) The ternary precursor comprises first particles and second particles of different particle sizes, and the mass ratio of the first particles to the second particles is 1:(1-5); (7) The molar ratio of the Li element in the lithium source to the ternary precursor is 0.95-1.
25.
8. The preparation method according to claim 6, characterized in that: Also includes at least one of the following features: (1) The lithium source includes at least one of hydrated lithium hydroxide, lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate and lithium oxalate; (2) The free lithium ion conversion agent contains N, and the N includes at least one of W, B, Mo, F, S, V, P and Cl; (3) The modification treatment is carried out in an ultrasonic environment, the frequency of the ultrasonic wave is 20 kHz to 50 kHz, and the ultrasonic time of the ultrasonic wave is 20 min to 40 min.
9. The preparation method according to claim 5, characterized in that: Also includes at least one of the following features: (1) The step of preparing the aqueous solution of the matrix material comprises: mixing the matrix material with deionized water and stirring uniformly, wherein the stirring speed is 20 Hz to 50 Hz; (2) The step of preparing the aqueous solution of the matrix material comprises: mixing the matrix material with deionized water and stirring them uniformly, wherein the stirring time is 20 min to 40 min; (3) The sintering temperature of the sintering treatment is 250°C to 500°C; (4) The sintering time of the sintering treatment is 6 h to 12 h; (5) The solid-liquid separation comprises subjecting the modified mixed material to a filter press treatment, wherein the extrusion pressure of the filter press is 0.2 MPa-0.5 MPa; (6) The solid-liquid separation comprises subjecting the modified mixed material to a filter press treatment, wherein the filter press time is 10 min to 30 min; (7) The solid-liquid separation comprises successively subjecting the modified mixed material to filter pressing and drying treatment, wherein the drying temperature is 80-170° C.; (8) The solid-liquid separation comprises successively subjecting the modified mixture to filter pressing and drying treatment, and the drying time is 1 to 3 hours.
10. A lithium ion battery, characterized in that: The positive electrode material comprises the positive electrode material as described in any one of claims 1 to 4, or comprises the positive electrode material prepared by the preparation method as described in any one of claims 5 to 9.
Citation Information
Patent Citations
High-compaction and high-stability high-nickel cathode material and preparation method thereof, and lithium ion battery
CN110010889A
Method for reducing content of residual alkali on surface of positive electrode material and application thereof
CN111453779A